Jewish Law, Roman Law, and the Accordance of Hospitality to Refugees and Climate-Change Migrants. Issue 1 (1st June 2021) - Ben-Nun, Gilad
Abstract: This article examines Jewish law's approach to forced migration. It explains the difference under Jewish law between forced migration brought about by disasters and the state of being a refugee—which is directly associated with war and armed conflict. It continues by demonstrating how these distinctions influenced the religious Jewish authors of the 1951 Refugee Convention. It concludes with the fundamental distinction between Jewish law and Roman law, concerning the latter's application of a strong differentiation between citizens and migrant foreigners, which under Jewish law was entirely proscribed as per the religious duty to accord hospitality to forced migrants irrespective of their background.